2022
DOI: 10.3389/fonc.2022.873649
|View full text |Cite
|
Sign up to set email alerts
|

DHW-221, a Dual PI3K/mTOR Inhibitor, Overcomes Multidrug Resistance by Targeting P-Glycoprotein (P-gp/ABCB1) and Akt-Mediated FOXO3a Nuclear Translocation in Non-small Cell Lung Cancer

Abstract: Multidrug resistance (MDR) is considered as a primary hindrance for paclitaxel failure in non-small cell lung cancer (NSCLC) patients, in which P-glycoprotein (P-gp) is overexpressed and the PI3K/Akt signaling pathway is dysregulated. Previously, we designed and synthesized DHW-221, a dual PI3K/mTOR inhibitor, which exerts a remarkable antitumor potency in NSCLC cells, but its effects and underlying mechanisms in resistant NSCLC cells remain unknown. Here, we reported for the first time that DHW-221 had favora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Similarly, dactolisib reversed drug resistance mediated by ABCB1 and ABCG2 in AML [ 77 ] and mesothelioma cell lines [ 78 ], respectively. Others such as perifosine [ 79 ], BEZ235 [ 80 ], and DHW-211 [ 81 ] have been reported to reverse drug resistance in ABCB1-overexpressing breast cancer, ovarian cancer, and NSCLC cell lines, respectively. We found that although HS-173 could inhibit ABCB1-mediated efflux of calcein-AM and ABCG2-mediated PhA efflux at higher concentrations ( Figure 5 ), HS-173 was unable to reverse the drug resistance mediated by ABCB1 or ABCG2 at sub-toxic concentrations ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dactolisib reversed drug resistance mediated by ABCB1 and ABCG2 in AML [ 77 ] and mesothelioma cell lines [ 78 ], respectively. Others such as perifosine [ 79 ], BEZ235 [ 80 ], and DHW-211 [ 81 ] have been reported to reverse drug resistance in ABCB1-overexpressing breast cancer, ovarian cancer, and NSCLC cell lines, respectively. We found that although HS-173 could inhibit ABCB1-mediated efflux of calcein-AM and ABCG2-mediated PhA efflux at higher concentrations ( Figure 5 ), HS-173 was unable to reverse the drug resistance mediated by ABCB1 or ABCG2 at sub-toxic concentrations ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of adrenocortical carcinoma to mitotane, DOX, etoposide, cisplatin and streptozotocin can be significantly enhanced by verapamil and tariquidar, which are known as competitive P-gp inhibitors and nontransporter P-gp inhibitors ( 78 ). DHW-221, a dual PI3K/mTOR inhibitor, has also been found to bind P-gp to competitively inhibit efflux function and downregulate P-gp ( 15 ). The triazolo[1,5-a]pyrimidine derivative WS-716 ( 79 ), some 1,4-substituted arylalkyl piperazine derivatives ( 80 ), pyrimidine aminobenzene derivatives ( 81 ), 5-phenylfuran derivatives characterized by alkyl-substituted phenols and 6,7-dimethoxy1,2,3,4-tetrahydroisoquinoline ( 82 ), and the 4-indolyl quinazoline derivative YS-370 ( 83 ) have been reported to be potential P-gp competitive inhibitors.…”
Section: Reversing Mdr By Inhibiting P-gpmentioning
confidence: 99%
“…TMDs consist of six transmembrane α-helical structures that provide specificity for substrates. Chemotherapy drugs that act as P-gp substrates are pumped out of tumor cells ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle Assay was performed according to a previous standard protocol. 24 The SW480 cells were treated with indicated concentrations of compound ZLHT-7 (0 μM, 1 μM, 2 μM and 4 μM) for 48 h with DMSO as a vehicle. Then, the cells were harvested, washed three times with PBS, and fixed with 70% cold ethanol overnight.…”
Section: Experimental Protocolsmentioning
confidence: 99%